Drivers of Customer Loyalty in the Downstream Petroleum Sub-Sector in Nigeria - Ogbunamiri, Chinanu; Agu, Agu Godswill (ARRUS Journal of Social Sciences and Humanities, 2022)
The downstream petroleum sub-sector in Nigeria has remained highly competitive since the partial subsidy removal era. Operators now adopt various marketing efforts to attract and retain customers. While several models have been used to examine the drivers of customer loyalty in the petroleum industry, no study is known that applies the 7Ps model. This study, attempts to close this gap. Data was generated from petroleum products customers in the Southeast region of Nigeria, and analyzed with the SPSS 23.0 multiple regression analysis. Findings reveal that all the 7Ps variables – product, price, place, promotion, people, process and physical evidence are significant drivers of customer loyalty. The study recommends appropriate blending of the mix elements for more positive outcomes.